Changing Health Professionals' Attitudes and Practice Behaviors Through Interprofessional Continuing Education in Oral‐Systemic Health. Issue 12 (1st December 2017) - Mowat, Stephanie; Hein, Casey; Walsh, Tanya; MacDonald, Laura; Grymonpre, Ruby; Sisler, Jeffrey
Abstract : Integration of oral‐systemic science into clinical care holds promise for improving patient outcomes and presenting opportunities for individuals in various health care professions to learn with, from, and about each other. The aim of this study was to examine whether an interprofessional continuing education program dedicated to oral‐systemic health improved participants' attitudes toward interprofessional education and collaboration between dental and non‐dental health care professionals and whether it influenced the physicians' practice of screening for debilitating oral diseases. The study took place in 2014 and used a mixed‐methods approach, consisting of Readiness for Interprofessional Learning Scale (RIPLS) surveys conducted before, immediately after, and six months after the intervention, as well as surveys of self‐reported practice behaviors and semi‐structured interviews. A total of 231 health care professionals participated in the lectures and roundtable discussions. Of those, 134 responded to the pre‐program survey (58% response rate), 110 responded to the post‐program survey (48% response rate), and 58 responded to the survey six months after the program (25% response rate). The participants' median total RIPLS score at baseline was 76.5, which increased significantly immediately following the program (81.0) but returned to baseline six months later (76.5). Participants' RIPLS domain scores also increased significantly by profession from before to after the event, with effects returning to baseline after six months. Significantly more physicians reported screening for caries and periodontal disease after the intervention. An overall theme of "learning with, from, and about each other" was drawn from the interviews with 15 participants. The physicians took away a message of "just look in the mouth, " while the dental professionals reported feeling valued as members of the health care team. Although reported improvements in oral‐systemic health practice immediately after the intervention were encouraging, further research is necessary to understand why collaborative behaviors were not sustained.